The Genetic Divergence and Phylogenetic Relationship of Indonesia Swamp Buffalo (Bubalus Bubalis) based on Partial Sequences of Cytochrome B Gene of Mitochondrial DNA - Winaya, Aris; Sukri, Akhmad; Gofur, Abdul; Amin, Mohammad (International Journal of Engineering and Technology, 2019)
The aim of this study was to determine the genetic divergence and genetic relationships among Indonesia swamp buffalo (Bubalus bubalis) based on cyt b gene partial sequence of mitochondrial DNA. The buffalo samples taken from seven biogeographic regions where representing the part of Indonesia island which consisted of Aceh, Riau, Madiun, Blitar, Lombok, South Kalimantan, and Tana Toraja. The results showed that based on the genetic value of the genetic distance of Indonesian buffalo was ranged between 0.00-0.08. The individual’s genetic distance that derived from the similar region tended to be lower than the genetic distance between individuals from different areas. The phylogenetic analysis showed that the groups of buffalo population have a genetic relationship where to correspond to their biogeographic origin. It indicated that any a close genetic relationship between the individual animal in the group that related to the bio-geographical area which compares to between group. The domestication of Indonesian buffalo presumably originated from China mainland and then spread to Indonesia island through Philippine and Malaysia. These results also supported the previous study that buffalo from Philippine was quite close the genetic relationship to Indonesia’s buffalo while Philippine’s buffalo was the closest relationship to China’s buffalo. Although this finding was not yet described in detail about the distribution of taxa because only used one parameter of cyt b gene, but in general, this study has described the genetics flow of Indonesian local buffalo that suspected be one of the genetics sources of the local buffalo in Indonesia.